Unbalanced inhibition on granular and mixed anammox sludge by different molecular weight fractions of unbiodegradable proportion of sludge anaerobic digestion reject water. (August 2021) - Wang, Shunyu; Gong, Hui; Ding, Jianning; Xu, Enhui; Cui, Rongrong; Yang, Dianhai; Gu, Guowei; Dai, Xiaohu
Abstract: Anaerobic ammonium oxidation (anammox) was a sustainable low-cost method to deal with high ammonia wastewater. Unbiodegradable proportion of sludge anaerobic digestion reject water demonstrated unbalanced inhibitory effects on specific anammox activity (SAA). The SAA of 0.155 gN·gVSS −1 ·d −1 (based on ammonia) was obtained with 50% raw pretreated reject water proportion. In contrast, SAA decreased to 0.061 gN·gVSS −1 ·d −1 with 100% raw pretreated reject water without dilution, about 60.65% of that at half dilution ratio. Comparing the SAA of granular and mixed anammox sludge, granular sludge demonstrated more resilience than mixed anammox with higher abundance at same sludge concentration. Unbalanced inhibition by different molecular weight fractions of reject water was observed. The SAA tests shown that the organics between 10 kDa and 30 kDa caused more severe inhibition on anammox activity, though the organic concentration in this molecular weight cut-off (MWCO) range was only accounted for limited proportion. Besides, the results of three-dimension excitation emission matrix fluorescence spectroscopy (EEM) and Fourier transform infrared spectra (FTIR) analysis demonstrated the existence of fulvic acid-like substances, tryptophan-like protein substances, carboxylic acid and derivatives and small amide groups in this MWCO range of unbiodegradable sludge digestion reject water. Graphical abstract: Unlabelled Image Highlights: The unbiodegradable proportion caused unbalanced inhibition on anammox. Granular sludge had advantages on enduring inhibition comparing with mixed sludge. Organic in range of 10 kDa – 30 kDa caused more severe inhibition on anammox EEM shown that Tryptophan-like protein substances existed in reject water. FTIR demonstrated carboxylic acid and derivatives, small amide groups existed.